Diasporic Transgressions of Commedia dell'arte. - Gherasim, Gabriel C. (Caietele Echinox, 2023)
Ever since its "birth certificate" on February 25, 1545, Commedia dell'arte's substantial resources of itineracy, improvisation, subversion, extraterritoriality, extemporaneity, laughter, and joy have unceasingly unveiled their essential mutability and ambiguity, prompting UNESCO's depiction of commedia as an "invisible and intangible cultural asset". The present study attempts to disclose the diasporic transgressions of Commedia dell'arte by considering four basic dimensions: the formal, the tropological, the topological, and the temporal, respectively. This approach further examines how and to what extent the diasporic transgressions of Commedia dell'arte can be elucidated by considering the afore-mentioned categories of explanation. Ultimately, the itinerant and improvisational character of Commedia dell'arte is explanatory for the mutations and developments within the four dimensions themselves.